Stock price informativeness, cross-listings, and investment decisions - Foucault, Thierry; Gehrig, Thomas (Journal of Financial Economics, 2008)
We show that a cross-listing enables firms to obtain, from the stock market, more precise information about the value of their growth opportunities. Thus, cross-listed firms make better investment decisions and trade at a premium. This theory of cross-listings implies that the sensitivity of investment to stock prices is larger for cross-listed firms. Moreover, the cross-listing premium is positively related to the size of growth opportunities and negatively related to the quality of managerial information. The sensitivity of the premium to the size of growth opportunities increases with factors that strengthen the impact of the cross-listing on price informativeness.